Modernisme Islam dalam Pemikiran Politik Deliar Noer di Indonesia - Fina Anggraini (Lembaga Yasin AlSys, 2026)
Although numerous studies have examined the relationship between Islam and politics in Indonesia, this article specifically analyzes Islamic modernism in the political thought of Deliar Noer and its relevance to the Indonesian nation-state context. The study aims to explain the main characteristics of Islamic modernism developed by Deliar Noer and to map his position on democracy, the state, and the role of religion in the public sphere. The method used is library research with a qualitative descriptive–analytical approach through a systematic review of Deliar Noer’s major works as primary sources and supporting literature as secondary sources. The findings show that Deliar Noer represents a strand of Islamic modernism that emphasizes the substantive and ethical dimensions of Islamic teachings, particularly morality, justice, and social responsibility without promoting the formalization of Islam as a state ideology. He accepts the principles of democracy, constitutionalism, and the nation-state insofar as they do not close off the political participation of Muslims and continue to provide space for Islamic values in the regulation of public life. However, the article also finds that Deliar Noer’s thought tends to be normative and does not elaborate in detail the institutional mechanisms for translating Islamic values into public policy. In conclusion, Islamic modernism in Deliar Noer’s political thought offers a moderate and contextual model of Islamic political thought for the Indonesian nation-state, but still requires further strengthening at the level of institutional design and empirical implementation to become more operational in contemporary political practice.